2020
DOI: 10.1007/s12230-020-09772-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potato Psyllid Vector Density and Time of Infection on Zebra Chip Disease Development after Harvest and during Storage

Abstract: Candidatus Liberibacter solanacearum" (Lso) (="Candidatus Liberibacter psyllarous") is an uncultured, phloem-limited bacterium that is associated with zebra chip disease (ZC) in potato (Solanum tuberosum L.) and transmitted by the potato psyllid (Bactericera cockerelli (Šulc)). Vector density and timing of infection have been shown to affect ZC prevalence at harvest; however, little work has been done on disease development during storage. Here we confirm with field-cage trials that ZC prevalence at harvest wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…Conversely, in Idaho, late-season infections are likely to occur [41], a pattern that may correspond to the increase in the number of potato psyllids captured in the field late in the season [44]. Time of infection is known to affect both the severity of ZC symptoms [17,18] and the Lso quantity within host plants. Likewise, our results showed that ZC symptom severity and Lso titer vary with the time of infestation (or infection).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, in Idaho, late-season infections are likely to occur [41], a pattern that may correspond to the increase in the number of potato psyllids captured in the field late in the season [44]. Time of infection is known to affect both the severity of ZC symptoms [17,18] and the Lso quantity within host plants. Likewise, our results showed that ZC symptom severity and Lso titer vary with the time of infestation (or infection).…”
Section: Discussionmentioning
confidence: 99%
“…At 4 DBVR, symptoms were not detectable at harvest. Although successful Lso translocation from leaves to tubers has been reported in potato plants infected 4 days before harvest [19], ZC symptom may not be observed for infestations that occur up to one week before harvest [15,17]. Lso detection success may also be limited in the late infestation times of 4 and 12 days before vine removal, as pathogen quantities are at undetectable levels; many tubers that are infected late in the season may proceed to test positive after a few months of storage [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations